Drug Prescription Knowledge and Practices among Dental Students and Interns Enrolled in Selected Yemeni Universities - Al-Wesabi, Mohammed Ali; Al-Sanaani, Saba; Al-Taybi, Shrooq; Binrugaan, Somya; Al-Raih, Altaf; Albashari, Abdullkhaleg; Ebrahem, Hisham Ebrahem (University of Science and Technology, Yemen, 2017)
Objective To assess the drug prescription knowledge among dental students and interns in public and private Yemeni universities. Methods A descriptive, observational study of drug prescription knowledge and practices was conducted through the distribution of self-administrated questionnaires to a total of 464 dental students and interns enrolled in four universities in Yemen in 2015. The study investigated the factors to be considered before drug prescribing, indications for prescribing antibiotics in dental situations, common antibiotics and analgesics prescribed, difficulties in writing a prescription and knowledge of the World Health Organizations Guide to Good Prescribing. Findings were presented as descriptive statistics of frequencies and percentages, and differences and associations were tested at P-values <0.05. Results The majority of respondents were females (65.9%; 304/464), being enrolled in public universities (54.1%; 251/464) and from the fifth level of study (54.9%; 251/464). The mean respondents age was 23.0 1.3 years (range: 2232). Presence of systemic diseases (75.0%), pregnancy status (72.2%) and presence of allergies (68.8%) were the factors most frequently considered by the respondents prior to drug prescribing. On the other hand, presence of abscesses was the most frequent reason for prescribing antibiotics (36.6%). Amoxicillin was the most frequently prescribed antibiotic (74.1%), while paracetamol (58.2%) and ibuprofen (47.0%) were the most frequently prescribed analgesics. Not knowing the brand names of prescribed drugs and wrongly filled prescriptions were the most frequent errors in writing prescriptions, being reported by 79.3% and 55.3% of respondents, respectively. Regarding the factors associated with common prescribing errors, female students had significantly more errors than their male counterparts regarding the posology and knowledge of brand names. In addition, fifth-level students reported significantly fewer errors in writing a drug prescription than fourth-level students, and the interns showed fewer errors than their undergraduate colleagues. Moreover, students from public universities reported significantly more errors in knowing brand names and duration of treatment than private university students. Conclusions Dental students enrolled at the fourth and fifth levels as well as in the internship year of dentistry have insufficient knowledge and skills in prescribing drugs used in the dental field because of the perceived gaps in clinical pharmacology courses during their study. Revising the timing and content of pharmacology courses in dental curricula is required in light of the positive aspects of those from the dental faculties worldwide, emphasizing on drug prescribing skills and preparing dental students well before the clinical levels of the study program.